)Qæ(NNDOARÆJSXKÆ TAÃMNICÆ uKRAÇNI (B/s)E - (NnALIWAJKO(B, (NsTEPAN )QæWANOWI^(B,s)E; )Qæ(NLX(B'Ã(NNKO(B, (Nl@DMILA(B,s)E ((NkI)QÇW (B:s)E (NpROSW)QÆTA(B,s)E, 2004)
(NaWTOR DOSL)QÆDVUÃ UKRAÇNSXKO(B-Æ(NNDÆJSXKÆ ETNÆ^NÆ(B, Æ(NSTORI^NÆ(B, (NMOWNÆ(B, (NFOLXKLORNÆ(B, (NETNOGRAFÆ^NÆ TA MÆFOLOGÆ^NÆ ZW(B'(NQZKI(B.s)E
(Nb)QÆBLÆOGR(B.: (NS(B. 441-445s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NfOLXKLORs -- (NeTNOGRAF)QÆQs)E